2014
DOI: 10.1371/journal.pone.0084292
|View full text |Cite
|
Sign up to set email alerts
|

Secretome Analysis of Human Oligodendrocytes Derived from Neural Stem Cells

Abstract: In this study, we investigated the secretome of human oligodendrocytes (F3.Olig2 cells) generated from human neural stem cells by transduction with the gene encoding the Olig2 transcription factor. Using mRNA sequencing and protein cytokine arrays, we identified a number of biologically important secretory proteins whose expression has not been previously reported in oligodendrocytes. We found that F3.Olig2 cells secrete IL-6, PDGF-AA, GRO, GM-CSF, and M-CSF, and showed prominent expression of their correspond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 93 publications
0
25
0
Order By: Relevance
“…In mice, administration of cuprizone, that damages and ablates oligodendrocytes, both oligodendrocytes and OPCs secrete IL-1β, a known pro-inflammatory cytokine [90][91][92]. CXCL1, CXCL2, CXCL3, CXCL5, and CXCL6 all bind the CXCR2 receptor, which is constitutively expressed on oligodendrocytes, but not present on astrocytes [88,93]. The CXCR2 receptor is upregulated in response to these cytokines that are secreted by oligodendrocytes, supporting autocrine regulation.…”
Section: Astrocytes and Oligodendrocytes Play Active Roles In Immune mentioning
confidence: 96%
See 1 more Smart Citation
“…In mice, administration of cuprizone, that damages and ablates oligodendrocytes, both oligodendrocytes and OPCs secrete IL-1β, a known pro-inflammatory cytokine [90][91][92]. CXCL1, CXCL2, CXCL3, CXCL5, and CXCL6 all bind the CXCR2 receptor, which is constitutively expressed on oligodendrocytes, but not present on astrocytes [88,93]. The CXCR2 receptor is upregulated in response to these cytokines that are secreted by oligodendrocytes, supporting autocrine regulation.…”
Section: Astrocytes and Oligodendrocytes Play Active Roles In Immune mentioning
confidence: 96%
“…Several CXCR2 ligands have previously been associated with OPC proliferation and differentiation [94], indicating that oligodendrocytes regulate their own proliferation. Granulocyte macrophage colony stimulating factor (GM-CSF) is upregulated in resting oligodendrocytes [93] which has been found to be anti-apoptotic for neurons and neuroprotective in models of stroke. Additionally, astrocytes secrete CXCL1 in spinal cord injury and in MS lesions, both in vivo and in vitro, which may act to recruit oligodendrocytes [88,95].…”
Section: Astrocytes and Oligodendrocytes Play Active Roles In Immune mentioning
confidence: 99%
“…Oligodendrocytes are glial cells responsible for the myelination of neurons in the CNS (Bradl & Lassmann, 2010). Recently, a secretome analysis demonstrated that oligodendrocytes were able to synthesize various laminin chains, including α2, α4, α5, β1, β2, β3, γ 1 and γ 2 (Kim et al, 2014), suggesting that these cells are able to generate most laminin isoforms. The exact laminin isoforms synthesized by oligodendrocytes, however, remain unknown.…”
Section: (E) Oligodendrocytesmentioning
confidence: 99%
“…In addition, neuroprotective effects of the secretome of NSCs have been demonstrated after spinal cord injury in mice [21] and after intracerebellar injection of NSCs in mouse models of Machado-Joseph disease [28]. The responsible factors in the secretome of NSCs and OPCs have been determined [22,[29][30][31]. Also in this study, human iPSC-derived OPCs appeared to express a similar set of factors and were able to reduce the EAE clinical score in mice after intraventricular injection, mainly by reducing cell infiltration and lesion size.…”
Section: Discussionmentioning
confidence: 99%